2016
DOI: 10.1117/12.2216227
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of spiculated breast lesions

Abstract: Virtual clinical trials are a promising new approach increasingly used for the evaluation and comparison of breast imaging modalities. A key component in such an assessment paradigm is the use of simulated pathology, in particular, simulation of lesions. Breast mass lesions can be generally classified into two categories based on their appearance; nonspiculated masses and spiculated masses. In our previous work, we have successfully simulated non-spiculated masses using a fractal growth process known as diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The number of images rated equally good in both 2D and DBT were 60.4% for simulated and 86% for real images. This is a significant improvement on the previous observer study results 10 conducted with simulated lesions without adding blending effects as shown in Table 1. …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The number of images rated equally good in both 2D and DBT were 60.4% for simulated and 86% for real images. This is a significant improvement on the previous observer study results 10 conducted with simulated lesions without adding blending effects as shown in Table 1. …”
Section: Resultssupporting
confidence: 65%
“…The width of the spicule observed in the DBT stack was also measured at several key points. A 3D horn structure could then be fitted using an empirically observed power law 10 to model the change in width with distance from the lesion core Figure 1d. Then random distortions were applied to the cones to reduce the geometric appearance.…”
Section: Generating Biologically-inspired Spiculated Massesmentioning
confidence: 99%
“…The spicules were modeled following a technique by Elangovan et al (2016). In their research, the authors detailed a method for generating spiculated lesions, which involved creating a central mass through a diffusionlimited algorithm and then attaching a set of spicules to the surface of this mass generated using patient data.…”
Section: Addition Of Spiculationsmentioning
confidence: 99%
“…The features extracted from real masses are then used to generate digital models. Elangovan et al (2016b) extended the DLA model to simulate spiculated lesions by using features, in terms of spicule length, width, curvature and distribution, extracted from patient DBT images containing spiculated lesions. These features were used as a guide to simulate realistic spicules which were then attached to the surface of a DLA mass resulting in models as shown in figure 8(a).…”
Section: Statistical Models Based On Characteristics Of Real Lesionsmentioning
confidence: 99%